Trauma Healing sebagai Instrumen Perlindungan Hukum terhadap Anak Korban Konflik Sosial di Negeri Masihulan, Maluku Tengah - Eka Dahlan Uar; Syah Awaluddin; Ridwan F. Lestaluhu; Muhammad Saleh Suat; Umar Kelebia; Afrinda Afrinda; Putri Nabila Husein (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The social conflict that occurred in Negeri Masihulan, Central Maluku Regency, in April 2025, resulted in dozens of residents' houses burning down and had serious psychological impacts, especially for children. Children as a vulnerable group experience fear, anxiety, and trauma due to conflict and displacement situations. This community service aims to provide psychosocial assistance through trauma healing as an effort for non-litigation legal protection for child victims of social conflict. This activity was carried out using the approach of playing, drawing, telling stories, and praying together, attended by 30 children aged 5-13 years. The results of the activity showed positive changes in the emotional condition of children, a growing sense of security, and an increased spirit of togetherness after the conflict. Trauma healing has proven to be an effective instrument in psychological recovery as well as a form of implementation of community-based legal protection. It is hoped that this activity will become a model in handling child victims of conflict in areas prone to social conflict in Maluku.